WISATA SASTRA PADA PUISI PAHLAWAN KERJA KARYA H.R. SUBRANTAS DI CAGAR BUDAYA MONUMEN KERETA API - Rangkuti, Listi Mora (Magistra Andalusia: Jurnal Ilmu Sastra, 2023)
Literature and tourism is a new approach that connects literature with tourism. This approach is very important given the close connection between a literary work and the setting of the place that is told in the work. With this linkage, literary works also contribute to the progress of tourism. If we look at the poetry of Pahlawan Kerja, there is literary tourism that reflects poetry and it’s strong relationship with the Cultural Heritage site, the Railway Monument and the Heroes Cemetery. Using Lucien Goldmann's genetic structural theory, H.R Soebrantas' poem Pahlawan Kerja is analyzed so that literary tourism that reflects history, culture, and religion is found.